2010
DOI: 10.1097/sla.0b013e3181cf8ed0
|View full text |Cite
|
Sign up to set email alerts
|

Sacral Nerve Stimulation for Fecal Incontinence

Abstract: Sacral nerve stimulation using InterStim Therapy is a safe and effective treatment for patients with FI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 316 publications
(62 citation statements)
references
References 67 publications
5
55
0
2
Order By: Relevance
“…In the sham arm there was a median of 6.9 FIEs per week, but with a slightly higher rate of passive FI (median 3.0 episodes) than urge episodes (median 2.5 episodes) ( Table 4). Hysterectomy, a n (%) 30 (29) 24 (24) Vaginal operation, a n (%) 3 (3) 2 (2) Pelvic operation, a n (%) 19 (18) 16 (16) Abdominal operation, n (%) 28 (24) 30 (27) Anal operation, n (%) 6 (5) 9 (8) Neck or back pain, n (%) 15 (13) 21 (19) OAB, n (%) 15 (13) 7 (6) Diverticular disease, n (%) 4 (3) 6 (5) Irritable bowel syndrome, n (%) 1 (1) 4 (4) a Females only (% calculated from females only). …”
Section: Bowel Diary Data At Baselinementioning
confidence: 99%
See 3 more Smart Citations
“…In the sham arm there was a median of 6.9 FIEs per week, but with a slightly higher rate of passive FI (median 3.0 episodes) than urge episodes (median 2.5 episodes) ( Table 4). Hysterectomy, a n (%) 30 (29) 24 (24) Vaginal operation, a n (%) 3 (3) 2 (2) Pelvic operation, a n (%) 19 (18) 16 (16) Abdominal operation, n (%) 28 (24) 30 (27) Anal operation, n (%) 6 (5) 9 (8) Neck or back pain, n (%) 15 (13) 21 (19) OAB, n (%) 15 (13) 7 (6) Diverticular disease, n (%) 4 (3) 6 (5) Irritable bowel syndrome, n (%) 1 (1) 4 (4) a Females only (% calculated from females only). …”
Section: Bowel Diary Data At Baselinementioning
confidence: 99%
“…[22][23][24][25][26][27][28] SNS has become the first-line surgical treatment option for FI. 17 Despite largely favourable data, SNS requires two operations and is not without risk of morbidity.…”
Section: Management Of Faecal Incontinencementioning
confidence: 99%
See 2 more Smart Citations
“…However, the complication rate among the 665 patients who had permanent SNS electrode implantation was ∼15%, resulting in permanent removal of the device in 18 (2.7%) patients 67. A multicenter, prospective nonrandomized trial, not included as part of the previous meta-analysis, reported that 83% of 106 patients had ≥50% improvement in FI at 12 months and 40% became fully continent 62. Improvements were sustained for 3 years 61,62.…”
Section: Resultsmentioning
confidence: 99%